Salt resistance of species of the Chenopodiaceae family (Amaranthaceae s.l.) in the desert part of the Syrdarya River Valley, Kazakhstan - BEKTEMIR B. OSMONALI; POLINA V. VESSELOVA; GULMIRA M. KUDABAYEVA; SALAVAT DUISENBAYEV; OMIRZHAN TAUKEBAYEV; KANAT ZULPYKHAROV; SERIKBAY USSEN; DAULET SH. ABDIILDANOV (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Osmonali BB, Vesselova PV, Kudabayeva GM, Duisenbayev S, Taukebayev O, Zulpykharov K, Ussen S, Abdildanov DSH. 2024. Salt resistance of species of the Chenopodiaceae family (Amaranthaceae s.l.) in the desert part of the Syrdarya River Valley, Kazakhstan. Biodiversitas 25: 4162-4170. Salt tolerance is a complex ecological strategy: halophytes have adaptive physiological and anatomical modifications to ‘combat’ the damaging effects of osmotic and metabolic stress that cause impaired growth and reproduction. Halophytes are represented in many angiosperm families that are distributed worldwide. Halophytes represent a heterogeneous group of plants that combine representatives of different taxa, life forms, ecological types, and floras. The family Chenopodiaceae belongs to the largest and oldest families in arid territories of the globe. It occupies the leading position in the spectrum of families of the desert floras of Kazakhstan. The choice of the study region—the desert part of the Syrdarya River Valley within Kyzylorda oblast, Republic of Kazakhstan—is conditioned by a wide distribution of saline territories within its limits, to which the overwhelming majority of species of the studied family are confined. The objects of the study are phytocenoses (communities) located in saline and non-saline areas with the participation or dominance of Chenopodiaceae (Amaranthaceae s.l.) species in the desert part of the Syrdarya River Valley. Distribution of studied taxa on preference to one or another degree of salinity at genus level showed certain peculiarities. In particular, it was revealed that species of genera Atriplex, Caroxylon, and Bassia grow, as a rule, on soils from non-saline to slightly saline. In turn, species of the Suaeda genus prefer to settle on soils of medium and high saline. Finally, the species categorized as hyperhalophytes (preferring a high degree of salinity) belong exclusively to one subfamily, Salicornioideae. This indicates a certain direction of evolution of the adaptive characteristics of representatives of this family.